The burden of anaemia among displaced women and children in refugee settings worldwide, 2013–2016. Issue 6 (11th November 2019) - Kay, Ariel; Leidman, Eva; Lopez, Velma; Wilkinson, Caroline; Tondeur, Melody; Bilukha, Oleg
Abstract : Introduction: Displaced persons have a unique risk for developing anaemia due to often limited diets, overcrowding, new infections and inadequate sanitation and hygiene. The lack of anaemia prevalence estimates among the displaced inhibit global planning for anaemia reduction. Methods: We analysed population representative, cross-sectional nutrition surveys from 2013 to 2016 conducted by the United Nations High Commissioner for Refugees and partner agencies. Included surveys measured haemoglobin concentration among children 6–59 months, non-pregnant women 15–49 years, or both groups. For each survey, we calculated mean haemoglobin and prevalence of total anaemia (<110 g/L in children, <120 g/L in women), and classified public health severity following WHO guidelines. Pearson correlations between indicators from women and children surveys were calculated where both subpopulations were measured. Results: Analysis included 196 surveys among children and 184 surveys among women from 121 unique refugee settings in 24 countries. The median prevalence of total anaemia in children and women was 44% and 28%, respectively. Sixty-one per cent of child surveys indicated a problem of severe public health importance compared with 25% of surveys in women. The prevalence of total anaemia in children and women was strongly correlated (ρ=0.80). Median prevalence of total anaemia was approximately 55% greater and mean haemoglobin was 6 g/L lower among children age 6–23 months compared with children 24–59 months. West and Central Africa region had the highest median prevalence of anaemia both in women and children. Conclusion: While the burden of anaemia is high among the displaced, it mirrors that of the general population. Haemoglobin should continue to be measured in nutrition surveys in refugee settings. Sustained, multisectoral efforts to reduce anaemia are needed, with specific focus on children under 2 years of age and refugee settings in the West and Central Africa region.